PERAN SISTEM ADMINISTRASI MANUNGGAL SATU ATAP DALAM UPAYA PENCEGAHAN DAN PENANGGULANGAN PEMALSUAN SURAT-SURAT KENDARAAN BERMOTOR (Studi di SAMSAT UPTB Kota Manado) - BAWANGO, PHYLIA; RUMAPEA, PATAR; POMBENGI, JERICHO DANGA (Sam Ratulangi University, 2017)
Abstract:This research aims to explain about the role of technical implementing unit of Manado city or samsat Manado inpreventing and overcoming counterfeiting of motor vehicle letters. This research uses descriptive method of qualitativeapproach, and data collection technique done by observation, interview technique, and documentation. The number ofinformants as many as 10 people. In this research using the measurement of duties and functions of the samsat office interms of where the approach of this process include (i) planning, (ii) coordination, (iii) coaching, (iv) control of servicetasks. The result of the research shows that the role of samsat manado in prevention against counterfeiting of motor vehicleletters is : a. Conducting motor vehicle document research by conducting cross check against frame number and enginenumber to motor vehicle; b. Receive and examine the results of physical inspection of motor vehicles to be adjusted to thedocuments of motor vehicles; c. The selection of good safety signs in the motor vehicle letters, so that the letter of the motorvehicle is difficult to forge. Countermeasures of criminal counterfeiting of letters conducted by samsat Manado party byblocking motor vehicle letters. The role of samsat in this case only as an informant only. Samsat has no authority ininvestigating cases of counterfeiting of motor vehicles letters. Samsat still cooperate with the police if the police still needthe help of samsat for completeness of ranmor files or as expert witnesses.Keywords : Role, SAMSAT, Counterfeiting